ANALISIS DAERAH RAWAN LONGSOR DI KECAMATAN WAY KRUI TAHUN 2015 - Catur Pangestu W; I Gede Sugiyanta; Rosana Rosana (JPG (Jurnal Penelitian Geografi), 2015)
This research aimed to know the characteristics of areas prone to landslide based on a prone landslide map in Way Krui sub district year 2014. The map was classified according to the prone area so it produced A area as the less prone to erosion, B area as the prone to erosion, C area as the less prone, D area as the prone landslide and E very vulnerable to landslide. This research was using overlay methods. Objects of this research were the landslide map. The subject in research was areas less to landslide in Way Krui sub district Pesisir Barat. The results of research were A area was less prone, B was prone area, C area was less prone, D area and the E area were very prone and in recommended to local conservation.The analysis which was gotten showed that parameter wich was dominant in way krui sub-district is settlement.Penelitian ini bertujuan untuk mengetahui karakteristik daerah rawan longsor berdasarkan Peta Rawan Longsor di Kecamatan Way Krui tahun 2014. Peta tersebut digolongkan menurut area rawan sehingga menghasilkan area A sebagai daerah yang kurang rawan longsor, area B rawan longsor, area C kurang rawan, area D rawan longsor dan area E sangat rawan terhadap longsor. Penelitian ini menggunakan metode overlay. Objek dalam penelitian yaitu peta parameter longsor. Subjek dalam penelitian yaitu daerah rawan longsor di Kecamatan Way Krui Kabupaten Pesisir Barat. Hasil penelitian area A kurang rawan, area B rawan, area C kurang rawan, Area D rawan dan area E sangat rawan dan di sarankan untuk daerah konservasi. Analisis yang didapatkan bahwa parameter yang dominan di Kecamatan Way Krui adalah permukima.Kata kunci: daerah rawan longsor, overlay, parameter longsor.